Sintesis Membran Mikrofilter Zeolit Dengan Perekat Semen Dan Aplikasinya Untuk Pengolahan Air Laut Menjadi Air Tawar - Ruliatima Ruliatima; Riyanto Utomo (Jurnal Maritim Polimarin, 2017)
In this study zeolite-cement membranes have been synthesized with different zeolite and cement mass ratios to obtain three types of membranes, namely Z1S, Z2S and Z3S. Semen functions as an adhesive. Determination of membrane physics characteristics was obtained that the density of each Z1S, Z2S and Z3S membranes in sequence was 1, 44 g / cm3, 1.41 g / cm3 and 1.33 g / cm3 and the fluxes were 0.40 kg respectively. h-1.m-2, 1.41 kg.h-1.m-2 and 2.22 kg.h-1.m-2. Membrane applications for processing seawater into fresh water provide good results.